Estudo numérico e experimental da dinâmica não-linear de um giroscópio - Silva, Rosiney Desidério da (2012)
The present work proposes a study of the dynamics of a gyroscope using simulated data of an analytical model by comparing with experimental data. Classical mechanical modeling approaches are used to identify the equilibrium points, stability and verification of the regions where the motion equations of the gyroscope can present regular or chaotic behavior. The Lyapunov exponents are identified through the standard method, Eckmann-Ruelle Method, Wolf method with time series and the 0-1 test. The results achieved illustrate the main advantages and drawbacks of each method and allow to observe qualitatively and quantitatively information about the motion of the gyroscope used.